Pemodelan Kualitas Air Sungai Cikakembang akibat Pembuangan Limbah Organik Menggunakan HEC-RAS - Yudha Primus Kristianto; Doddi Yudianto; Finna Fitriana (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2025)
The Cikakembang River, a tributary of the Citarum River in Majalaya District, has been polluted due to domestic and textile industrial activities. Although the Citarum Harum program, initiated in 2018, has been considered successful in improving water quality in the Citarum River, pollution in the Cikakembang River remains a serious issue. This study aims to analyze the impact of organic waste disposal on the water quality of the Cikakembang River using HEC-RAS. The modeling results obtained are then used as a basis for formulating pollution control strategies. This study focuses on four water quality parameters: BOD, DO, NH₃-N, and TP. In addition to field measurements of various technical data, this study also includes laboratory testing of twelve (12) water samples taken along the Cikakembang River. The data obtained are used to calibrate a mathematical model with statistical bias and relative error analysis as the objective function. Based on water quality testing results, it was found that the concentrations of BOD, DO, NH₃-N, and TP in the Cikakembang River do not meet Class II water quality standards as stipulated in Government Regulation No. 22 of 2021. Furthermore, HEC-RAS simulation results with various pollution control scenarios indicate that the existing conditions cannot fully address the issue. Therefore, stricter monitoring measures are needed for wastewater quality discharged into the water bodies, including enhancing the capacity of wastewater treatment plants and optimizing river rehabilitation programs to sustainably reduce pollution in the Cikakembang River.